Vitamin D Plasma Levels and In-Hospital and 1-Year Outcomes in Acute Coronary Syndromes. Issue 19 (May 2015) - De Metrio, Monica; Milazzo, Valentina; Rubino, Mara; Cabiati, Angelo; Moltrasio, Marco; Marana, Ivana; Campodonico, Jeness; Cosentino, Nicola; Veglia, Fabrizio; Bonomi, Alice; Camera, Marina; Tremoli, Elena; et al.
<x xml:space="preserve">Abstract</x> Abstract Deficiency in 25-hydroxyvitamin D (25[OH]D), the main circulating form of vitamin D in blood, could be involved in the pathogenesis of acute coronary syndromes (ACS). To date, however, the possible prognostic relevance of 25 (OH)D deficiency in ACS patients remains poorly defined. The purpose of this prospective study was to assess the association between 25 (OH)D levels, at hospital admission, with in-hospital and 1-year morbidity and mortality in an unselected cohort of ACS patients. We measured 25 (OH)D in 814 ACS patients at hospital presentation. Vitamin D serum levels >30 ng/mL were considered as normal; levels between 29 and 21 ng/mL were classified as insufficiency, and levels < 20 ng/mL as deficiency. In-hospital and 1-year outcomes were evaluated according to 25 (OH)D level quartiles, using the lowest quartile as a reference. Ninety-three (11%) patients had normal 25 (OH)D levels, whereas 155 (19%) and 566 (70%) had vitamin D insufficiency and deficiency, respectively. The median 25 (OH)D level was similar in ST-elevation myocardial infarction (STEMI) and non-ST-elevation myocardial infarction (NSTEMI) patients (14.1 [IQR 9.0–21.9] ng/mL and 14.05 [IQR 9.1–22.05] ng/mL, respectively; P = .88). The lowest quartile of 25 (OH)D was associated with a higher risk for several in-hospital complications, including mortality. At a median follow-up of 366 (IQR 364–379) days, the lowest quartile of 25 (OH)D, after adjustment for the main confounding factors, remained significantly associated to 1-year mortality (P < .01). Similar results were obtained when STEMI and NSTEMI patients were considered separately. In ACS patients, severe vitamin D deficiency is independently associated with poor in-hospital and 1-year outcomes. Whether low vitamin D levels represent a risk marker or a risk factor in ACS remains to be elucidated.